Legal Fragmentation in Regional Environmental Governance: Evaluating Decentralized Mining Policies in Indonesia - Maulana Fahmi Idris (Universitas Sains dan Teknologi Komputer, 2026)
Legal fragmentation has become a significant challenge in decentralized environmental governance, particularly within extractive sectors in developing countries. This study examines how decentralized mining policies in Indonesia generate regulatory fragmentation and influence environmental governance performance across multiple administrative levels. A qualitative comparative case study approach is employed to analyze mining governance dynamics in selected regions with varying institutional capacities. Data were collected through semi-structured interviews with key stakeholders, including government officials, environmental regulators, civil society organizations, and local communities, complemented by systematic analysis of policy documents and regulatory frameworks. The data were analyzed using thematic comparative analysis to identify patterns of regulatory overlap, authority conflict, and policy inconsistency. The findings indicate that decentralization in the mining sector produces structural fragmentation characterized by overlapping regulations, weak intergovernmental coordination, and inconsistent policy implementation. These conditions are reinforced by divergent institutional priorities, where regional governments prioritize economic development while central authorities emphasize regulatory control and environmental protection. Such misalignment contributes to governance inefficiency and increases environmental risk. This study contributes to Multi-Level Governance and Institutional Fragmentation Theory by demonstrating that legal fragmentation is not merely an administrative issue but a structural governance condition shaped by institutional design and political-economic incentives. A regulatory fragmentation framework is proposed to explain how multi-level governance misalignment affects environmental outcomes in extractive industries. The study concludes that improving environmental governance in decentralized mining systems requires integrated regulatory coordination and strengthened multi-level governance mechanisms rather than relying solely on centralization reforms.